Compatible Study on Utilizing Frequency for Non-Invasive Electrical Resistance Tomography Using COMSOL Multiphysics - Yasmin, Abdul Wahab; Ruzairi, Abdul Rahim; Mohd Hafiz, Fazalul Rahiman; Leow, Pei Ling; Suzanna, Ridzuan Aw; Fazlul Rahman, Mohd Yunus; Herlina, Abdul Rahim; Herman, Wahid; Shafishuhaza, Sahlan; Mohd Amri, Md. Yunus; Norhaliza, Abdul Wahab; Azian, Abd Aziz (Penerbit Universiti Teknologi Malaysia, 2015)
Non-invasive techniques are widely applied in process plants compared to other sensing techniques. Due to advantages such as preventing corrosion to the sensor and lengthening the sensor lifespan, this technique is also applied in process tomography such as in non-invasive ERT system. The purpose of this paper is to investigate the compatibility of utilizing frequency for non-invasive ERT systems. Based on quasi-static electric fields, one pair of electrodes is used to simulate the optimum frequency for the system. It was firstly derived using a mathematical equation followed by simulation using finite element model software (COMSOL Multiphysics). Results showed that by simulating several frequencies to the system, a minimum frequency that should be applied is 2 MHz to ensure that the real part of the total impedance is dominant and also to neglect the reactance part of the total impedance for the non-invasive ERT system. Thus, the non-invasive ERT system is an alternative way for the industry in monitoring the performance of process plant.